(untitled) (Research, Society and Development, 2020)
This paper’s objective is to present a mapping of part of the brazilian scientific research that discusses the interrelationships between children’s literature and mathematic, aiming the teaching of later. For that, varied databases were consulted as research sources, among them the Brazilian Digital Library of Theses and Dissertations. (BDTD) IBICT and the Thesis Bank of the Coordination for the Improvement of Higher Education Personnel (CAPES), among others. This bibliographic research aims to understand how children’s literature can contribute to mathematic learning, in a way that can favor the construction of mathematical concept by kids of primary education. According to the analyzes, it is possible to conclude that Children’s Literature can contribute, for mathematical learning, towards the creation of learning contexts, mobilization of student’s interest, favoring communication and comprehension of reality, in addition to enabling mathematical lenguage to be worked together with the mother tongue and facilitate the notations that help in solving problems, which demonstrates that children’s literature constitute an important tool in the teaching and learning of mathmatics.